2013
DOI: 10.1021/nn3056077
|View full text |Cite
|
Sign up to set email alerts
|

Self-Limiting Electrodeposition of Hierarchical MnO2 and M(OH)2/MnO2 Nanofibril/Nanowires: Mechanism and Supercapacitor Properties

Abstract: Hierarchical nanostructures have generated great interest in the energy, materials, and chemical sciences due to the synergic properties of their composite architectures. Herein, a hierarchical MnO₂ nanofibril/nanowire array is successfully synthesized. The structure consists of a conformal layer of MnO₂ nanofibrils evenly distributed on the surface of the individual MnO₂ nanowires. The synthetic mechanism of this hierarchical structure is characterized by electrochemical measurements, Raman spectroscopy, EELS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
177
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(182 citation statements)
references
References 49 publications
4
177
1
Order By: Relevance
“…20 Raman spectroscopy was also used to analyze the MnO x structural features over large areas. 12 A Raman spectrum of the MnO x /CNT/ RGO is shown in Figure 3d, and the spectra of pristine graphite foil, CNT and RGO are shown in Supplementary Figure S9. The peak observed in Figure 3d at Raman shift of~640 cm − 1 can be attributed to the Mn-O stretching vibration in the basal plane of MnO 6 and/or the symmetric stretching vibration (Mn-O) of the MnO 6 group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Raman spectroscopy was also used to analyze the MnO x structural features over large areas. 12 A Raman spectrum of the MnO x /CNT/ RGO is shown in Figure 3d, and the spectra of pristine graphite foil, CNT and RGO are shown in Supplementary Figure S9. The peak observed in Figure 3d at Raman shift of~640 cm − 1 can be attributed to the Mn-O stretching vibration in the basal plane of MnO 6 and/or the symmetric stretching vibration (Mn-O) of the MnO 6 group.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the porous and flower-like structure could provide a large and accessible surface area to greatly enhance surface ion adsorption, improve the accessibility of cations and shorten the ion diffusion path. 2,17 The smaller and uniformly sized nanoparticles could also facilitate fast charge transfer on the surface or sub-surface of the active material; for example, Duay et al 12 found that the specific capacitance was much higher for small MnO 2 nanofibrils (5-10 nm) than for large MnO 2 nanowires (4.5 μm). In addition, although MnO x could be gradually oxidized to a higher valent state during the charge/discharge process, the structural features associated with the as-prepared MnO x , such as ionic (e.g., vacancies and misplaced ions) and electronic (electrons and holes) defects and mismatches at different phases, could still be preserved because of the slow and mild nature of the process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the searching for electrode materials with higher electrochemical performance are still seriously needed, because of the practical application of supercapacitors are hindered by their low specific capacitance, poor cycling stability and so on. Over the past few years, lots of transition metal oxides and metal hydroxide such as MnO 2 , NiO, Co 3 O 4 , Ni(OH) 2 , and NiAl-LDH [6][7][8][9][10][11][12][13][14], have been wildly studied, because of there lower price and lower toxic nature. However, the intrinsic low conductivity of these metal oxides limited the performance of the supercapacitors.…”
mentioning
confidence: 99%
“…Recently, hierarchically nanostructured TMO materials have gradually become a research hotspot in SC field because of their unique structures [63][64][65][66][67]. These structures could offer large specific surface area, abundant accessible electroactive sites, and short ion diffusion pathway during the rapid charge-discharge process [63][64][65][66][67].…”
Section: Introductionmentioning
confidence: 99%